2010
DOI: 10.2174/1874609811003020081
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Involvement of Lamins in Aging

Abstract: The molecular mechanisms that cause physiological aging are still not completely understood, most likely because of the complex nature of the aging process. Recent discoveries on segmental progeroid syndromes emphasize the importance of studying rare diseases to discover more common mechanisms. Since the identification of mutations in the LMNA gene that causes the segmental progeroid syndrome, Hutchinson-Gilford progeria syndrome (HGPS), there has been an increasing interest in the potential role for lamins in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Several progeroid disorders result from mutations in the genes encoding lamin A or ZMPSTE24 that interfere with the final proteolytic event that removes the modified tail [14], [17], [39][41]. The symptoms associated with these diseases range in severity and appear to correlate with the extent of the lamin A cleavage defect such that the greater the amount of uncleaved persistently prenylated prelamin A that accumulates, the more severe the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several progeroid disorders result from mutations in the genes encoding lamin A or ZMPSTE24 that interfere with the final proteolytic event that removes the modified tail [14], [17], [39][41]. The symptoms associated with these diseases range in severity and appear to correlate with the extent of the lamin A cleavage defect such that the greater the amount of uncleaved persistently prenylated prelamin A that accumulates, the more severe the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The unexpected discovery that double-null pharynx (smooth) muscles had significantly reduced pumping activity is, to our knowledge, the first evidence that LEM-domain proteins are required in smooth muscle. Whether LEM-domain proteins are required in human smooth muscle is unknown and warrants testing, since it suggests genetic links to human smooth muscle disease and might provide molecular insight into the vascular smooth muscle pathology of Hutchinson-Gilford progeria syndrome, which is caused by severe mutations in LMNA (Rodríguez and Eriksson, 2010). Collectively, our findings support the possibility that human LEM2 mutations might influence or cause EDMD.…”
Section: Discussionmentioning
confidence: 99%
“…6 Although the pathophysiologic mechanisms involved in laminopathies are not fully understood, alterations in the posttranslational maturation of prelamin A are important pathogenic events. [7][8][9] Indeed, before being assembled in the nuclear lamina as mature lamin A, prelamin A undergoes several maturation steps including addition of a farnesyl group followed by a proteolytic cleavage by the metalloprotease Zmpste24. We and others have demonstrated that FPLD2 and metabolic laminopathies are associated with an abnormal accumulation of prelamin A, possibly due to misrecognition of the mutated protein by Zmpste24.…”
mentioning
confidence: 99%